SERS from pyridine adsorbed on electrodispersed platinum electrodes - Bilmes, Sara Aldabe (1989)
SERS of pyridine adsorbed on electrodispersed platinum electrodes is reported. Electrodispersed platinum surfaces are obtained by electroreducing hydrous platinum oxide layers. The intensity of the Raman scattering for adsorbed pyridine is enhanced by at least one order of magnitude, after normalizing with respect to the area increase. The estimated Raman enhancement factor is lower than that reported for roughened silver electrodes but it is still sufficiently large to allow Raman scattering from adsorbates on platinum to be detectable. Surface changes (ageing) of the metal surface can be also followed by SERS.